Edukasi Kesehatan Reproduksi Pada Remaja Dalam Mencegah Penyimpangan Seksual SMK S Cokroaminoto Salongo - Sibuah, Siska; Ningsih, Suci Rahayu; Manika, Helkim Laode; Ahmad, Alviandra; Fauzan, Moh. Rizki (Cattleya Darmaya Fortuna, 2025)
This community service aims to direct the community, especially teenagers, to a healthy lifestyle related to reproductive health in preventing sexual deviations. The subjects of the service are vocational high school students who are vulnerable to the negative influence of social media and the environment. Reproductive health is very important for both men and women. Reproductive is defined as physical, mental and social well-being in order not to be free from disease or disability in all matters relating to the reproductive system, its functions and processes. Community service at SMKS Cokroaminoto Salongo is very necessary to be implemented using the location search method, approach to the school and student knowledge and insight into reproductive health and sexual deviations that they must avoid. Adolescent reproductive health is an inseparable part of psychological, mental and social health. Adolescents must understand and know their sexual reproductive health so as not to produce sexual deviations that will harm themselves and their families.